Optical Characterization of Thin Solid Films (Springer Series in Surface Sciences,, 2018)
This book is an up-to-date survey of the major optical characterization techniques for thin solid films. Emphasis is placed on practicability of the various approaches. Relevant fundamentals are briefly reviewed before demonstrating the application of these techniques to practically relevant research and development topics. The book is written by international top experts, all of whom are involved in industrial research and development projects.